PROSES PELAKSANAAN RITUAL KAKADIU BUKUNO KAMOKULANO LIWU PADA MASYARAKAT BOMBONAWULU DI KELURAHAN BOMBONAWULU KECAMATAN GU KABUPATEN BUTON TENGAH - Nurdin, Nurdin; Niampe, La; Syahrun, Syahrun (Jurnal Penelitian Budaya, 2021)
Abstract: The purpose of this study is to study and describe the kakaÄ‘iu Î²ukuno kamokulano liwu ritual process in Bombonawulu community, Gu District, Buton Tengah Regency. The study uses qualitative methods by presenting them in the formof descriptions. The location of this research is in Bombonawulu Village, Gu District,Central Buton Regency. Data collection with interviews, observations and documentation. This study, the authors used qualitative data analysis techniques. The results of this study indicate that the process of carrying out the kakaÄ‘iu Î²ukunokamokulano liwu ritual consists of five stages, namely: (1) the preparatory stage includes the preparation of the complete kakaÄ‘iu Î²ukuno kamokulano liwu ritual as well as checking the completeness of the ritual at the Daduwali Palace; (2) the steps to the Î²ukuno kamokulano liwu burial place, including: the procession of ritual executives, starting with the black flag bearer, the ritual executor and the group of men, then the group of women and white flag bearers, (3) stages in the dwelling place, including: doing worship, cleaning themselves, climbing the cliff, worshiping again and continuing to open the cover that wraps the Î²ukuno kamokulano liwu frame and (4) the bathing stage, includes: scraping the frame with coconut milk, then smearing it with coconut oil and water the bones with holy water ngkolaki, (5) haroa stage, including: reading congratulations and eating together.Keywords: Â Implementation, Â Ritual, Kakadiu, Bukuno, Kamokulano,Liwu